FOOD AND FEEDING OF TWO SPECIES OF GREY MULLETS VALAMUGIL BUCHANANI (BLEEKER) AND LIZA VAIGIENSIS QUOY AND GAIMARD INHABITING BRACKISHWATER ENVIRONMENTS IN SRILANKA - Wijeyaratne, M J S; Costa, H H (Indian Journal of Fisheries, 2011)
Valamugil buchanani and Liza vaigiensis were observed to be omnivorous grazers feeding mainly on serpulidpolychaetesanddetritus. Considerable amount of sand were also presentin the stomach contents. Seasonalvariation in the abundance of different food items in the diet was observed for both species. In~V. buchanani,the gastrosomatic index was found to be relatively low during their breeding season. The relative gutlength of V. buchanani increased significantly with the size of fish. However, the amounts of plant matterand animal matter in the diet did not change significantly with size. The values calculated for similarityindices indicate that there is high or moderate overlap among the diets of different size groups of bot hspecies.